MODIFIKASI REAKTOR DRUM UNTUK PRETREATMENT PENGOLAHAN LIMBAH CAIR PADA HOME INDUSTRY TAHU DAN TEMPE - Thamrin, Sulaiman Hamzani; Syarifudin A; Pahruddin, M (UPPM Poltekkes Kemenkes Banjarmasin, 2022)
Liquid waste in the case of tofu industrial waste has a variety of very high organic matter content, if it is not processed properly it will pollute the environment. Based on the results of research on the waste from the tempe-tofu factory, it is known that the pH is 4.3; TSS 140 mg/L; COD 4506.6 mg/L; and BOD 1285.59 mg/L. To meet quality standards, it must be processed first with the right technology before being disposed of so as not to pollute the environment. The problems faced by Partners 1 and Partners 2 are that the factory does not provide funds specifically for processing, has limited land and does not understand the proper processing of liquid waste, is not aware of the impact on the environment, and lacks reuse of waste for other benefits. The purpose of this Community Service Community Partnership Program is to educate and apply appropriate technology for home industrial wastewater treatment (case study of Mitra 1 (tempe) and Mitra 2 (tofu) factories in Banjarbaru City) in an effort to reduce pollutant content. The service methods carried out include data collection, dissemination of research results; tool application, technical guidance, monitoring and evaluation. The results of the community service activities that have been carried out are carrying out outreach activities and coordination with Partners 1 (tempe factory) and Partner 2 (tofu factory), sharing and exposing research results involving relevant agencies, making drum reactors and technical guidance on equipment installation, monitoring and evaluation of community service activities. Through Community Service Activities, the Community Partnership Program is expected to provide benefits for increasing the understanding and skills of the tofu-tempe home industry as partners regarding the application of appropriate technology for liquid waste management. In addition, it is also hoped that a better network of cooperation will be established. Keywords: modification, drum reactor, liquid waste, tofu-tempe, minimize pollutant